2019
DOI: 10.1017/s104795111900009x
|View full text |Cite
|
Sign up to set email alerts
|

Transcatheter closure of doubly committed subarterial ventricular septal defects with the Amplatzer ductal occluder: initial experience

Abstract: Background:There is limited experience about transcatheter closure of doubly committed subarterial ventricular septal defects with Amplatzer ductal occluder.Methods:Between March, 2015 and July, 2017, a total of 22 patients with doubly committed subarterial ventricular septal defects received transcatheter closure using Amplatzer ductal occluder and underwent clinical follow-up for at least 6 months.Results:Device implantation was finally successful in 21 (95.4%) patients despite failed occlusion in one patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…The highest reported incidence of TR in the early period was 25.49% (26/102 patients) [29]. However, it was 40.91% (9/22 patients) for AR [18]. A review of reports showed a decrease in the incidence of these lesions over time, involving more tricuspid valve.…”
Section: Resultsmentioning
confidence: 95%
“…The highest reported incidence of TR in the early period was 25.49% (26/102 patients) [29]. However, it was 40.91% (9/22 patients) for AR [18]. A review of reports showed a decrease in the incidence of these lesions over time, involving more tricuspid valve.…”
Section: Resultsmentioning
confidence: 95%
“…18 With the accumulation of interventional experience, some studies proved perventricular closure of DCVSD with occluder was technically feasible and safe in the selected patients, and perventricular occlusion was the preferred approach because it showed a higher success rate than transfemoral occlusion. 19,20 No acute complications or severe adverse events (death, valve injury, complete atrioventricular block, and embolism) occurred either in the early period or during the follow-up in their research. 19,20 Even though interventional occlusion had been extensively applied in the treatment of peri-membranous and muscular ventricular septal defect, its application to DCVSD to some extent had been limited due to the complexity and its potential damages to the aortic valve.…”
Section: Discussionmentioning
confidence: 97%
“…19,20 No acute complications or severe adverse events (death, valve injury, complete atrioventricular block, and embolism) occurred either in the early period or during the follow-up in their research. 19,20 Even though interventional occlusion had been extensively applied in the treatment of peri-membranous and muscular ventricular septal defect, its application to DCVSD to some extent had been limited due to the complexity and its potential damages to the aortic valve. 21 Liu et al reported the incidence of early and late complications of interventional occlusion for DCVSD was up to 19.2% and 3.8%, respectively.…”
Section: Discussionmentioning
confidence: 97%
“…The incidence of cancellation due to heart conduction disturbances was smaller than that of the VSD PMO type. 9,10 Another study revealed that aortic valve disorders occur in 5-8% of the PMO-type VSD and 30% of the DCSA type, because the DCSA VSD is located just below the aortic valve. In the case of DCSA VSD, the aortic valve disorder occurs initially in the diastolic phase due to the venturi effect produced by the left-to-right shunt, then prolapse can occur during the systolic phase because the damaged aortic valve is no longer able to withstand high aortic pressure.…”
Section: Discussionmentioning
confidence: 99%